Determination of parameters of reliability-oriented maintenance of coal mine dump trucks - Chernyh V.G.; Otrokov A.V.; Grinko D.A.; Grinko A.A.; Mironova A.O.; Bogatyrev A.R. (Горное оборудование и электромеханика)
In today's world, where technology is developing at an incredible rate, and requirements for safety and production efficiency are becoming more stringent, a risk-based approach to mining equipment maintenance is very relevant. The article presents an approach to determining the indicators of reliability-oriented maintenance of quarry dump trucks. The study is based on an analysis of data on failures of dump truck components operated at one of the mining enterprises of the Kuznetsk coal basin. The paper defines the main statistical indicators: mathematical expectation, variance, intensity and failure rate. The intensity and frequency of failures are determined in relation to the proposed random variable distribution law, which allows us to obtain a more accurate picture of the reliability of equipment and its potential risks. A technique for determining the criticality of equipment is presented, which makes it possible to perform a qualitative and quantitative assessment of the failure risks of technical systems of a mining dump truck. Based on the results obtained, technical recommendations are proposed, in the form of the "PF interval" curve concept, for effective planning of mining equipment repairs, ensuring the determination of the time of functional and parametric failures of technical systems of a mining dump truck. The recommendations are based on the principles of reliability-oriented maintenance and make it possible to use the capital and fixed assets of a mining enterprise more efficiently.